Inflammation, depression and cardiovascular disease in women: the role of the immune system across critical reproductive events. (May 2019) - Mattina, Gabriella F.; Van Lieshout, Ryan J.; Steiner, Meir
Women are at increased risk for developing depression and cardiovascular disease (CVD) across the lifespan and their comorbidity is associated with adverse outcomes that contribute significantly to rates of morbidity and mortality in women worldwide. Immune-system activity has been implicated in the etiology of both depression and CVD, but it is unclear how inflammation contributes to sex differences in this comorbidity. This narrative review provides an updated synthesis of research examining the association of inflammation with depression and CVD, and their comorbidity in women. Recent research provides evidence of pro-inflammatory states and sex differences associated with alterations in the hypothalamic–pituitary–adrenal axis, the renin–angiotensin–aldosterone system and the serotonin/kynurenine pathway, that likely contribute to the development of depression and CVD. Changes to inflammatory cytokines in relation to reproductive periods of hormonal fluctuation (i.e. the menstrual cycle, perinatal period and menopause) are highlighted and provide a greater understanding of the unique vulnerability women experience in developing both depressed mood and adverse cardiovascular events. Inflammatory biomarkers hold substantial promise when combined with a patient's reproductive and mental health history to aid in the prediction, identification and treatment of the women most at risk for CVD and depression. However, more research is needed to improve our understanding of the mechanisms underlying inflammation in relation to their comorbidity, and how these findings can be translated to improve women's health.